Bridging sociology of religion to transition to adulthood: The emerging role of religion in young adults’ lives - Jung, Gowoon (Social compass, 2020)
The sociology of religion has not systematically explored the emerging roles of religion in the whole process of the transition to adulthood, especially in the changing contexts of delayed and complicated transitions to adulthood. Seeking to bridge the two different fields of sociology, we identify four directions of research: (1) a multidimensional approach that identifies the different dimensions of religion with varying degrees of relationship to young adults’ lives; (2) a close attention to racial/ethnic variation in the roles of religion for the transition to adulthood; (3) an open inquiry into the changing importance of religion for young adults in a rapidly shifting neoliberal global economy; and (4) the detrimental effects of religion in the transition to adulthood. We call for more research on the increasingly complex relationship between religion and the transition to adulthood.